Knee deep in innovation: advancing osteoarthritis therapy through regenerative medicine and precision interventions - Rastogi, Aavrati; Kalia, Roop B.; Meena, Pradeep K. (International Journal of Research in Medical Sciences, 2025)
Knee osteoarthritis (KOA) is a complex, heterogeneous illness that includes abnormal joint remodelling, chronic inflammation, mechanical strain, and metabolic dysregulation. It is not just a disease of cartilage loss. Its increasing prevalence highlights the critical need for disease-modifying approaches beyond palliation, particularly in older and obese individuals.